Challenges and Novel Strategy for Electric Vehicle Integration in Power System - Case Study Libya - Ibrahim Imbayah,; Yasser F. Nassar,; Yuosef Adraider,; Abdulgader Alsharif,; Hala El-Khozondare,; Abdussalam Ali Ahmed, (African Journal of Advanced Pure and Applied Sciences, 2024)
this paper investigates the challenges of Electric Vehicle (EV) integration in the grid system of Libya. To examine the effects of various EV penetration scenarios on Libya's generation a study is carried out. Increased peak demand, two-way power flows from vehicle-to-grid technology, and the requirement for further investment in charging infrastructure are among the major issues that have been identified. An innovative technique is suggested. Coordinated charging and vehicle-to-grid control algorithms are used to provide Libyan electric grid services and move EV load to off-peak times. The results guide other developing countries in bolstering their power infrastructure and achieving sustainable transportation goals.